Financial Village Standing in Indonesian Financial System - Herry Purnomo (Universitas Muhammadiyah Sidoarjo, 2015)
Financial resources of the village that are sourced from a country or a Regional Finance Financial based Law Number 6 Year 2014 of The Village is the mandate of the law that must be allocated to the village. The interconnectedness of the financial position of the village in the financial system of the country or Region concerned the Financial administrative and territorial relations, and there is no setting directly regarding the finances of the village as part of the financial system of the country or the financial area. In respect of the elements of the crime of corruption deeds against financial irregularities of the village there are still disagreements on the interpretation of the law in trapping the perpetrators of corruption on the village chief that implies not satisfy the principle of legality and legal certainty in the ruling of the matter of financial irregularities. In fact, many of the village chief or Councilor caught the criminal offence of corruption over the use of financial irregularities. This research analyzes How the financial position of the village in the financial system of the country or region, as well as whether the financial resources of the village is derived from the state budget or region budget managed in village budget belongs to the category of village finances and whether tort against the financial management of the village can be categorized as a criminal act corruption.